The New Peruvian Code of Constitutional Procedure - Eguiguren Praeli, Francisco José (2004)
The text highlights the relevance and significant impact of the approval of the Peruvian Constitutional Procedural Code, enacted by Law No. 28237. This Code not only represents a step forward in the consolidation of the constitutional processes recognised in Peru, but is also a pioneering model in Latin America, thanks to its systematic and comprehensive approach. For this reason, the author highlights the improvements introduced by the new regulatory body, with particular emphasis on the processes of habeas corpus, amparo, habeas data, popular action and unconstitutionality. As can be seen, the new Code seeks to strengthen the protection of fundamental rights, as well as a correct control of the constitutionality and legality of the norms that make up the national legal system. Despite its limitations and some undesirable changes, the Code conveys a message of innovation and raises hopes for a more effective judiciary committed to the protection of constitutional rights.